THE INTERPLAY OF MEDICAL, SOCIO–CULTURAL AND SYSTEMIC DRIVERS OF MATERNAL AND NEWBORN MORTALITY IN ANKA LGA, ZAMFARA, NIGERIA - Muhammad, Habibu; Almu, Bello; Yahaya, Manir; Aliyu, Ibrahim; Salisu, Dauda; Malan, Bashar Lawali (FUDMA Journal of Sciences, 2025)
Maternal and newborn mortality remains a critical public health challenge in Nigeria, with the burden disproportionately high in rural northern regions. This study investigated the complex interplay of medical, socio-cultural, and systemic drivers of maternal and newborn mortality in Anka Local Government Area, Zamfara State. A descriptive cross-sectional survey was conducted among 237 women of reproductive age, utilizing a health guided by the Health Belief Model, this study used a cross-sectional survey design and a structured questionnaire to collect data on socio-demographic characteristics, medical complications, socio-economic and cultural determinants, and health service availability. Findings revealed that nearly half (46%) of women experienced obstetric complications, primarily eclampsia (13.9%), obstructed labor (12.2%), and hemorrhage (10.1%). Alarmingly, over half (51.9%) reported losing a baby, while skilled birth attendance was low (47.7%). Key barriers included lack of awareness (32.1%), limited decision-making autonomy (67.1% decisions made by husbands), and distance to facilities. Although most women acknowledged available health services, significant concerns emerged regarding emergency readiness and inconsistent drug supply. The study concludes that maternal and newborn mortality in Anka LGA results from interconnected medical risks, deep-rooted socio-cultural practices, and systemic health service failures. Sustainable reduction requires integrated interventions addressing community awareness, economic empowerment, and substantial strengthening of primary healthcare quality and emergency obstetric care.